PERANCANGAN SIGN SYSTEM PADA DESA SADE LOMBOK TENGAH - Alfryan Tribuana P Repi; Sandi Justitia Putra; Danang Adi Wiratama (Universitas Mercu Buana, 2020)
Sade Village is an ecotourism atau ecotourism that is one of the tourism activities that is environmentally minded with the priority of nature conservation aspects, aspects of economic socio-cultural empowerment of local people as well as aspects of learning and education located in The Rembitan Village of Pujut Sub-District, Central Lombok. As one of the heritage attractions with an area of 5.5 hectares, Sade Village desperately needs the existence of a communicative and informative sign system for those who will assist wisatwan / visitors in accessing every facility in Sade Village. This research will design the work of sign system with the application of environtmental sign system concept with an atmosphere that remains authentic with Sade Village, which makes visitors still feel the rural atmosphere of sasak tribe. The design method used by the author is the design thinking method. The expected result in this study is the creation of environtmental sign system that makes visitors able to make the most of Sade Village facilities while traveling.